2019
DOI: 10.1214/19-ejs1618
|View full text |Cite
|
Sign up to set email alerts
|

Convergence rates for the generalized Fréchet mean via the quadruple inequality

Abstract: For sets Q and Y, the generalized Fréchet mean m ∈ Q of a random variable Y , which has values in Y, is any minimizerThere are little restrictions to Q and Y. In particular, Q can be a non-Euclidean metric space. We provide convergence rates for the empirical generalized Fréchet mean. Conditions for rates in probability and rates in expectation are given. In contrast to previous results on Fréchet means, we do not require a finite diameter of the Q or Y. Instead, we assume an inequality, which we call quadrupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Paper [BGKL18] provides upper and lower bounds on convergence rates for empirical barycenters in the context of the Wasserstein space over the real line. Independently of the present contribution, [Sch18] studies a similar problem and provides results complementary to ours.…”
supporting
confidence: 77%
“…Paper [BGKL18] provides upper and lower bounds on convergence rates for empirical barycenters in the context of the Wasserstein space over the real line. Independently of the present contribution, [Sch18] studies a similar problem and provides results complementary to ours.…”
supporting
confidence: 77%
“…They attempt, among others, to achieve asymptotic results in expectation, thus going beyond the standard results which hold in probability. While Ahidar‐Coutrix et al (2019) rely on a compact parameter space and use concentration inequalities, adapting Schötz (2019) to our scenario, one allows for a noncompact parameter space, by replacing the Lipschitz condition p1,p2P:1emρ(),qp1ρ(),qp2trueρ˙()qdP(),p1p20.5emnormala.normals. with a quadrupole condition involving the metrics d P on P and d Q on Q , p1,p2P,q1,q2Q:1emρ(),q1p1ρ(),q1q2ρ(),q2p1+ρ(),q2p22dQ(),q1q2dP(),p1p2. The bias of a Fréchet mean arises, among others, from curvature present. On a Riemannian manifold, using a series expansion of the metric in terms of Riemann normal coordinates in the tangent space at the population mean and a moment expansion up to the third order of the lifted probability measure, Pennec (2019) has shown that E[]expμ1()μn=scriptO()n1. Here the proportionality constant depends on the first covariant derivative of the curvature tensor.…”
Section: Fréchet Means and Their Limiting Behaviormentioning
confidence: 99%
“…For spaces that are not smoothly embedded in ambient space, and extrinsic means which are unique orthogonal projections from Euclidean means assumed at foci points in ambient space, Schötz (2019) has given examples with arbitrary smeary and antismeary (faster than 1/n but not sticky, see below) rates.…”
Section: Fréchet Means and Their Limiting Behaviormentioning
confidence: 99%
See 2 more Smart Citations